Some New Operations of (Î±,Î²,Î³) Interval Cut Set of Interval Valued Neutrosophic Sets - Mehmet Åahin; Vakkas UluÃ§ay; Merve MenekÅe (Institute for Research and Community Services (LPPM) ITB, 2018)
In this paper, we define the disjunctive sum, difference and Cartesian product of two interval valued neutrosophic sets and study their basic properties. The notions of the (Î±,Î²,Î³) interval cut set of interval valued neutrosophic sets and the (Î±,Î²,Î³) strong interval cut set of interval valued neutrosophic sets are put forward. Some related properties have been established with proof, examples and counter examples.